Public private partnership policy in Nigeria's infrastructure development landscape : a critical appraisal of the infrastructure Concession Regulatory Act - Soyeju, Olufemi Olugbemiga (University of Pretoria, 2015)
Dissertation (LLM)--University of Pretoria, 2014